THE EFFECTIVENESS OF GOOGLE CLASSROOM FOR ONLINE DISCUSSIONS - Mujad Didien Afandi; Tiyas Saputri (Universitas Muhammadiyah Makassar, 2020)
Covid-19 pandemic brings massive impacts to many life sectors, especially education. Schools and colleges are closed temporarily so that online learning is the only way to continue the education. Of many online platforms and media found on internet, Google Classroom provides features to support the online active learning activities. Therefore, this study is aimed at investigating the effectiveness of Google Classroom for online discussions.By involving 39 sixth-semester students of English Education Program – Universitas Nahdlatul Ulama Surabaya (UNUSA), this descriptive qualitative study captured the comment threads on Google Classroom as the data to describe the number of comments and participants in online discussions. Those data were collected and interpreted to prove that the platform supported written online discussions.The results found that the total number of comments found in 14 meetings was 457 comments which were mostly dominated by the students. The findings showed the students’ increasing participation in online discussions. Google Classroom with its features enables them to minimize the psychological barriers, provide attention, support and motivation in sharing ideas in written comments. Furthermore, notifications sent automatically to the students’ Gmail account is an advantage. In conclusion, Google Classroom is effective to increase the students’ participation in online discussions. With the features provided in the online platform, the students build up more enthusiasm, motivation, attention and support to share comments and ideas during online discussions. Thus, the use of this platform should be taken as a consideration when oral discussions do not work as expected.